Dominican Republic Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
The Dominican Republic could sustain a strong economic performance in the medium-term, but there are many pending key challenges to become a high-income and more equitable society by 2030. Although growth rates for the DR are projected to be around 5 percent for 2018-2020, the country faces structural challenges to fostering a more dynamic private sector that can create better jobs and ensure social inclusion. This SCD identifies five key and interrelated challenges which the DR needs to overcome to achieve a more inclusive and sustainable growth.